The care of the dead in late antiquity - Rebillard, Éric (Cornell studies in classical philology ;, 2009)
In this provocative book Éric Rebillard challenges many long-held assumptions about early Christian burial customs. For decades scholars of early Christianity have argued that the Church owned and operated burial grounds for Christians as early as the third century. Through a careful reading of primary sources including legal codes, theological works, epigraphical inscriptions, and sermons, Rebillard shows that there is little evidence to suggest that Christians occupied exclusive or isolated burial grounds in this early period. In fact, as late as the fourth and fifth centuries the Church did not impose on the faithful specific rituals for laying the dead to rest. In the preparation of Christians for burial, it was usually next of kin and not representatives of the Church who were responsible for what form of rite would be celebrated, and evidence from inscriptions and tombstones shows that for the most part Christians didn't separate themselves from non-Christians when burying their dead. According to Rebillard it would not be until the early Middle Ages that the Church gained control over burial practices and that "Christian cemeteries" became common. In this translation of Religion et Sépulture: L'église, les vivants et les morts dans l'Antiquité tardive, Rebillard fundamentally changes our understanding of early Christianity. The Care of the Dead in Late Antiquity will force scholars of the period to rethink their assumptions about early Christians as separate from their pagan contemporaries in daily life and ritual practice.